Nenhuma bacia é apenas uma bacia! - Gisela Pires do Rio; Claudio Egler; Otamar Carvalho; Margarida Mattos (Confins)
In this paper we provide an overview of the water management in the Paraiba State. The empirical analysis of this management is articulated around interviews with local and regional actors. We argue that under specific physical geographical conditions of the semi-arid region studied, we need to take into account the institutional issues as well the geographical spaces’ articulation to discuss a sustainable water management.